Circulating Cell-Free mtDNA Content as a Non-invasive Prognostic Biomarker in HCC Patients Receiving TACE and Traditional Chinese Medicine - Zhou, Guanlin; Li, Ying; Li, Shicheng; Liu, Hongxia; Xu, Fei; Lai, Xiaohuan; Zhang, Qiong; Xu, Jingxiang; Wan, Shaogui (Frontiers in Genetics, 2021)
Hepatocellular carcinoma (HCC) accounts for 70%-85% of liver cancer and about 85% of HCC are hepatitis B virus-related (HBV-HCC) in China. Transarterial chemoembolization (TACE) combined with traditional Chinese medicine (TCM) has been reported as an effective treatment. Potential biomarkers to straitify patients who may benefit from this treatment are needed. In this study, we aimed to evaluate whether circulating cell-free mitochondrial DNA (ccf-mtDNA) content was associated with the outcome of HCC patients, especially of those who received combination treatment of TACE and TCM. Univariate and multivariate Cox analyses were conducted to evaluate the association between ccf-mtDNA content and overall survival of HBV-HCC patients. Kaplan-Meier analysis was used to compare survival differences between patients with low and high ccf-mtDNA content. In a hospital-based cohort with 141 HBV-HCC patients, there was no statistically significant association between the ccf-mtDNA content and overall survival of HBV-HCC patients in the univariate analysis, but a borderline significant association was found in the multivariate analyses. In a subcohort of 50 HBV-HCC patients who received TACE and TCM treatment, high ccfDNA content conferred an increased death risk with an HR of 4.01 (95%CI: 1.25-12.84, p = 0.019) in the multivariate analysis. Kaplan-Meier survival analysis also showed that patients with high ccf-mtDNA content had unfavorable survival (Log Rank p = 0.097). Our findings suggest that ccf-mtDNA content is a potential non-invasive prognostic biomarker in HCC patients receiving TACE and TCM treatment.